The Influence of Creativity on Welfare Through Self-Efficacy in the Lake Toba Area of Samosir District - Nalom Siagian; Darma Manalu; Artha Lumban Tobing; Natalia E Sihombing; Jhonson Pasaribu (Postgraduate, University of Mataram, 2024)
This research aims to analyze the influence of creativity, business interest and self-efficacy on community welfare in the Lake Toba area of Samosir Regency as a tourist attraction, using IBM AMOS path analysis with a sample of 200 people spread across nine sub-districts. This research uses primary data and secondary data collected using the Liskert scale and field observations. The results of the research show that creativity has a direct effect on community welfare, creativity has a direct effect as evidenced by the value (p) = 0.000 < 0.05. Self-efficacy is able to mediate creativity to improve welfare with the result t = 13.15092246 > t table (0.05; 200-4) = 1.972141. Therefore, the first, second and sixth hypotheses in this research can be accepted. Business interests have a direct influence on community welfare. This can be proven by the value (p) = 0.000 < 0.05 while business interest on self-efficacy has no effect with value (p) = 0.34 > 0.05 and self-efficacy is unable to mediate business interest to improve community welfare with calculated t value = -0.93118348 < t table (0.05; 200-4) = 1.982597 then the third hypothesis is accepted while the fourth hypothesis and the seventh hypothesis are rejected.